Golf balls
A golf ball coating composition with a specific polyester polyol and hexamethylene diisocyanate formulation addresses abrasion resistance and flexibility issues, enhancing durability and spin performance.
Patent Information
- Application Number
- JP2020192127
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-11-25
- Filing Date
- 2020-11-19
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2040-11-19
AI Technical Summary
Existing golf ball coatings lack sufficient abrasion resistance and flexibility, leading to issues with durability and spin performance.
A golf ball coating composition comprising a urethane paint with a specific ratio of polyester polyol and hexamethylene diisocyanate isocyanurate and adduct forms, achieving an elastic work recovery rate of 70% or more, enhancing abrasion resistance and flexibility.
The coating composition provides high abrasion resistance, self-healing properties, and maintains high spin performance, improving the overall durability and aesthetic appearance of the golf ball.
Smart Images

Figure 0007615631000001 
Figure 0007615631000002 
Figure 0007615631000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a coating composition for a golf ball and a golf ball using the coating composition. [Background technology]
[0002] In order to protect the surface of a golf ball or to maintain a good aesthetic appearance, the surface of the ball is often coated with a paint composition. As a paint composition for such golf balls, a two-component curing polyurethane paint in which a polyol and a polyisocyanate are mixed immediately before use is preferably used because of its resistance to large deformation, impact, and friction (for example, Patent Document 1).
[0003] A common trend in recent golf ball development is to further reduce the spin rate on full shots with a driver, and due to this trend toward lower spin rates, the cover, which is the outermost layer, tends to become softer.
[0004] In addition, many golf balls have a core, a cover positioned outside the core, and a coating layer positioned outside the cover. Making this coating layer soft often has certain effects, such as contributing to the stability of the spin speed of the golf ball and providing excellent durability (for example, Patent Document 2).
[0005] Furthermore, a paint for golf balls has been developed that uses only one type of polyester polyol as the polyol component.
[0006] However, the abrasion resistance of the coating layer surface is not good, and there is room for further improvement. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2003-253201 A [Patent Document 2] JP 2011-67595 A [Patent Document 3] JP 2002-53799 A Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a paint composition for golf balls that can improve the abrasion resistance of the coating film, and a golf ball using the same. [Means for solving the problem]
[0009] As a result of intensive research by the present inventors in order to achieve the above-mentioned object, it was found that for a coating composition mainly composed of a urethane coating consisting of a polyol and a polyisocyanate, by using two types of polyisocyanate, an isocyanurate and an adduct of hexamethylene diisocyanate as the polyisocyanate and by preparing the coating composition so that the elastic work recovery rate of the composition is 70% or more, the coating film obtained from this coating composition has excellent yellowing resistance and flexibility, and in particular, by using two types of adduct, which has excellent flexibility, and a relatively tough isocyanurate, high spin performance can be obtained, which led to the completion of the present invention.
[0010] Therefore, the present invention provides the following Golf balls to provide. 1. A golf ball having a core, and a cover consisting of one or more layers covering the core, the outermost layer of the cover being a paint layer formed from a paint composition, each layer of the cover being formed from a resin composition, the resin composition having an elastic work recovery rate of 35% or more, and the paint composition being The main component is a urethane paint consisting of a polyol as the base agent and a polyisocyanate as the hardener. A coating composition, The polyol is composed of only one type of polyester polyol, and the polyisocyanate contains two types of hexamethylene diisocyanate, an isocyanurate and an adduct. ,and the above paint A golf ball comprising a composition having an elastic work recovery rate of 70% or more. 2. the above paintThe elastic work recovery rate of the composition according to the above item 1 is 80% or more. Golf balls . 3. 3. The method according to claim 1 or 2, wherein the mixing ratio (A) / (B) of the isocyanurate of hexamethylene diisocyanate to the adduct (B) is 95 / 5 to 40 / 60 by mass ratio. Golf balls . 4. The above coating composition has an elastic work recovery rate (W1) and each layer of the cover has an elastic work recovery rate (W2), and the value of W1-W2 is 50% or less. 1 The golf ball described herein. Effect of the Invention
[0011] The coating composition for golf balls of the present invention has a high self-repairing function, high abrasion resistance, excellent yellowing resistance and flexibility, and furthermore, provides high spin performance. Golf balls coated with the coating composition can have various improved performances. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The present invention will now be described in further detail. The golf ball paint of the present invention is composed mainly of a urethane paint made of a polyol and a polyisocyanate.
[0013] The polyol is not particularly limited, but it is preferable to use one or more kinds of polyester polyols. In particular, it is preferable to use two kinds of polyester polyols, polyester polyol (A) and polyester polyol (B), as the main agent. These two kinds of polyester polyols have different weight average molecular weights (Mw), and it is preferable that the weight average molecular weight (Mw) of the (A) component is 20,000 to 30,000, and the weight average molecular weight (Mw) of the (B) component is 800 to 1,500. The weight average molecular weight (Mw) of the (A) component is more preferably 22,000 to 29,000, and even more preferably 23,000 to 28,000. On the other hand, the weight average molecular weight (Mw) of the (B) component is more preferably 900 to 1,200, and even more preferably 1,000 to 1,100.
[0014] The above two types of polyester polyols are obtained by polycondensation of a polyol and a polybasic acid. Examples of the polyol include diols such as ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, diethylene glycol, dipropylene glycol, hexylene glycol, dimethylolheptane, polyethylene glycol, and polypropylene glycol, triols, tetraols, and polyols having an alicyclic structure. Examples of polybasic acids include aliphatic dicarboxylic acids such as succinic acid, adipic acid, sebacic acid, azelaic acid, and dimer acid, aliphatic unsaturated dicarboxylic acids such as fumaric acid, maleic acid, itaconic acid, and citraconic acid, aromatic polyvalent carboxylic acids such as phthalic acid, isophthalic acid, terephthalic acid, trimellitic acid, and pyromellitic acid, dicarboxylic acids having an alicyclic structure such as tetrahydrophthalic acid, hexahydrophthalic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, and endomethylenetetrahydrophthalic acid, and tris-2-carboxyethyl isocyanurate. In particular, polyester polyols having a cyclic structure introduced into the resin skeleton can be used as the polyester polyol of component (A), and examples thereof include polyester polyols obtained by polycondensation of a polyol having an alicyclic structure such as cyclohexanedimethanol with a polybasic acid, or polycondensation of a polyol having an alicyclic structure with a diol or triol with a polybasic acid. On the other hand, as the polyester polyol of component (B), a polyester polyol having a multi-branched structure can be used, and an example thereof includes polyester polyols having a branched structure such as "NIPPOLAN 800" manufactured by Tosoh Corporation.
[0015] The weight average molecular weight (Mw) of the entire base material consisting of the two kinds of polyester polyols is preferably 13,000 to 23,000, more preferably 15,000 to 22,000. The number average molecular weight (Mw) of the entire base material consisting of the two kinds of polyester polyols is preferably 1,100 to 2,000, more preferably 1,300 to 1,850. If these average molecular weights (Mw and Mn) deviate from the above ranges, the abrasion resistance of the coating film may decrease. The weight average molecular weight (Mw) and number average molecular weight (Mn) are measured values (polystyrene equivalent values) by gel permeation chromatography (hereinafter abbreviated as GPC) measurement by differential refractometer detection.
[0016] The amounts of the above two types of polyester polyols (A) and (B) are not particularly limited, but it is preferable that the amount of the (A) component is 20 to 30 mass % based on the total amount of the base material, and the amount of the (B) component is 2 to 18 mass % based on the total amount of the base material.
[0017] When only one type of polyol is used, it is preferable to use the polyester polyol (A) described above.
[0018] On the other hand, the polyisocyanate used in the present invention includes two types of isocyanurate and adduct of hexamethylene diisocyanate. Usually, isocyanate prepolymers are divided into three types of structures (adduct, biuret, and isocyanurate). Adduct refers to an addition product of diisocyanate and trimethylolpropane. Isocyanurate refers to a trimer of diisocyanate.
[0019] The above-mentioned hexamethylene diisocyanate also includes modified products thereof. Examples of modified products of hexamethylene diisocyanate include polyester modified products and urethane modified products of hexamethylene diisocyanate.
[0020] The mixing ratio (A) / (B) of the isocyanurate (A) of hexamethylene diisocyanate and the adduct (B) is preferably 95 / 5 to 40 / 60, more preferably 80 / 20 to 55 / 45, by mass ratio. When the ratio of the adduct (B) is increased within the above mixing ratio range, scratch resistance and spin properties tend to improve, but when the ratio of the adduct (B) is increased beyond the above range, there is a risk of deterioration in stain resistance.
[0021] Examples of nurates of hexamethylene diisocyanate (HMDI) include trade names "Coronate 2357" (manufactured by Tosoh Corporation), "Sumidur N3300" (manufactured by Sumika Covestro Urethanes), "Duranate TPA-100" (manufactured by Asahi Kasei Corporation), "Takenate D170N", "Takenate D177N" (both manufactured by Mitsui Chemicals, Inc.), and "Burnoc DN-980" (manufactured by DIC Corporation). These may be used alone or in combination of two or more.
[0022] Examples of adducts of hexamethylene diisocyanate (HMDI) include products with the trade names "Coronate HL" (manufactured by Tosoh Corporation), "Takenate D160N" (manufactured by Mitsui Chemicals, Inc.), "Duranate E402-80B", "Duranate E405-70B" (all manufactured by Asahi Kasei Corporation), "Burnoc DN-955", and "Burnoc DN-955S" (all manufactured by DIC Corporation). These products may be used alone or in combination of two or more.
[0023] The molar ratio (NCO group / OH group) of the hydroxyl group (OH group) of the polyester polyol used in the present invention to the isocyanate group (NCO group) of the polyisocyanate is preferably 0.6 or more, more preferably 0.65 or more, and the upper limit is preferably 1.5 or less, more preferably 1.0 or less, and even more preferably 0.9 or less. If this molar ratio is less than 0.6, unreacted hydroxyl groups remain, which may deteriorate the performance and water resistance of the coating film for golf balls. On the other hand, if it exceeds 1.5, the isocyanate groups become excessive, which may generate urea groups (brittle) by reaction with moisture, which may result in deterioration of the performance of the coating film for golf balls.
[0024] As the curing catalyst (organometallic compound), an amine catalyst or an organometallic catalyst can be used. As this organometallic compound, metal soaps such as aluminum, nickel, zinc, tin, etc., which have traditionally been used as curing agents in two-component curing urethane paints, can be suitably used.
[0025] The above-mentioned golf ball paint composition may contain known paint compounding ingredients, if necessary. Specifically, suitable amounts of thickeners, ultraviolet absorbers, fluorescent brighteners, slipping agents, pigments, etc. may be added.
[0026] In addition, the elastic work recovery rate of the paint composition for golf balls must be 70% or more, and is preferably 80% or more. If the elastic work recovery rate of the paint deviates from the above range, the abrasion resistance may deteriorate. Thus, in the present invention, the coating film formed on the surface of the golf ball has high elasticity, so that it has a high self-repairing function and is very excellent in abrasion resistance. In addition, the performance of the golf ball coated with the above paint composition can be improved. The method for measuring the elastic work recovery rate of the paint composition for golf balls will be described later.
[0027] The elastic work recovery rate is one of the parameters of the nanoindentation method, which is an ultra-microhardness test method that controls the indentation load on the order of micronewtons (μN) and tracks the indenter depth at the time of indentation with nanometer (nm) accuracy, and evaluates the physical properties of the coating. Conventional methods could only measure the size of the deformation mark (plastic deformation mark) corresponding to the maximum load, but the nanoindentation method can obtain the relationship between the indentation load and the indentation depth by automatically and continuously measuring. Therefore, it is considered that the physical properties of the coating can be evaluated with high accuracy without individual differences such as those observed when visually measuring the deformation mark with an optical microscope as in the conventional method. Since the coating on the surface of a golf ball is greatly affected by the impact of a driver or various clubs, and the effect of the coating on the physical properties of the golf ball is not small, measuring the coating for golf balls with the ultra-microhardness test method and performing the measurement with higher accuracy than the conventional method is a very effective evaluation method.
[0028] When using the above coating composition, the coating composition of the present invention can be prepared at the time of coating a golf ball manufactured by a known method, applied to the surface by adopting a normal coating process, and then dried to form a coating layer on the ball surface. In this case, the coating method can be suitably a spray coating method, an electrostatic coating method, a dipping method, or the like, and is not particularly limited.
[0029] As described above, the coating composition for golf balls uses polyester polyol as a base agent and polyisocyanate as a curing agent, and various organic solvents can be mixed depending on the coating conditions. Examples of such organic solvents include aromatic solvents such as toluene, xylene, and ethylbenzene, ester solvents such as ethyl acetate, butyl acetate, propylene glycol methyl ether acetate, and propylene glycol methyl ether propionate, ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone, ether solvents such as diethylene glycol dimethyl ether, diethylene glycol diethyl ether, and dipropylene glycol dimethyl ether, alicyclic hydrocarbon solvents such as cyclohexane, methylcyclohexane, and ethylcyclohexane, and petroleum hydrocarbon solvents such as mineral spirits.
[0030] The drying process may be carried out in the same manner as for known two-component curing urethane paints, and the coating composition of the present invention may be dried at a temperature of about 40°C or higher, particularly 40 to 60°C, for a drying time of 20 to 90 minutes, particularly 40 to 50 minutes.
[0031] The thickness of the paint layer is not particularly limited, but is preferably 3 to 50 μm, and more preferably 5 to 20 μm.
[0032] The coating composition can be used on any type of golf ball, such as a one-piece golf ball, a two-piece solid golf ball consisting of a core and a cover encasing the core, or a multi-piece solid golf ball consisting of one or more layers of a core and a multi-layer cover encasing the core.
[0033] The present invention also provides a golf ball having a core and a cover consisting of one or more layers covering the core, in which the outermost layer of the cover has a paint layer formed from the above-mentioned paint composition.
[0034] The cover is a member that covers the core and has at least one layer, such as a two-layer cover or a three-layer cover. In the case of a two-layer cover, the inner layer may be referred to as an intermediate layer, and the outermost layer as an outermost layer. In the case of a three-layer cover, the layers may be referred to, from the innermost layer, as an envelope layer, an intermediate layer, and an outermost layer. In addition, a large number of dimples are usually formed on the outer surface of the outermost layer to improve aerodynamic characteristics.
[0035] The material of each layer of the cover is not particularly limited, and may be, for example, an ionomer resin, a polyester resin, a polyamide resin, or a polyurethane resin. For example, the intermediate layer may be made of an ionomer resin or a highly neutralized ionomer resin, and the outermost layer may be made of a polyurethane resin.
[0036] The resin composition forming each layer of the cover preferably has an elastic work recovery of 35% or more, more preferably 43% or more. If the elastic work recovery of the resin composition is out of the above range, the scratch resistance of the cover material and the coating film may be deteriorated. The elastic work recovery is one parameter of the nanoindentation method for evaluating the physical properties of the cover (each layer), and the measurement method is the same as the measurement method of the elastic work recovery of the coating composition described above.
[0037] Furthermore, if the elastic work recovery rate of the paint composition is W1 and the elastic work recovery rate of each layer of the cover is W2, with regard to the relationship between these, if the difference between them is too large, the adhesion between the coating film and the cover will deteriorate and the coating film will become more likely to peel off, so the value of W1-W2 is preferably 50% or less, more preferably 40% or less, and even more preferably 30% or less.
[0038] The core can be formed using a known rubber material as the base material. Known base rubbers such as natural rubber or synthetic rubber can be used as the base rubber. More specifically, it is recommended to mainly use polybutadiene, particularly cis-1,4-polybutadiene having at least 40% or more of a cis structure. In addition, natural rubber, polyisoprene rubber, styrene butadiene rubber, etc. can be used in combination with the above-mentioned polybutadiene in the base rubber as desired. Polybutadiene can be synthesized using Ziegler catalysts such as titanium-based, cobalt-based, nickel-based, and neodymium-based catalysts, and metal catalysts such as cobalt and nickel.
[0039] The above base rubber may be blended with co-crosslinking agents such as unsaturated carboxylic acids and their metal salts, inorganic fillers such as zinc oxide, barium sulfate, calcium carbonate, and organic peroxides such as dicumyl peroxide and 1,1-bis(t-butylperoxy)cyclohexane, etc. Also, commercially available antioxidants and the like may be added as necessary.
[0040] In this way, the coating film formed with the above-mentioned paint composition has excellent abrasion resistance, and a golf ball coated with the paint composition can have improved performance, such as being able to prevent a significant decrease in spin performance even when repeatedly hit with a golf club. EXAMPLES
[0041] The present invention will be described in more detail below with reference to Synthesis Examples, Examples and Comparative Examples, but the present invention is not limited to the following Examples.
[0042] [Examples 1 to 5, Comparative Examples 1 to 3] A rubber composition for the core was prepared according to the formulation shown in Table 1, and then vulcanized at 155°C for 15 minutes to produce a core with a diameter of 36.3 mm. Next, the surrounding layer and intermediate layer were successively coated with various resin materials shown in the same table by injection molding. The surrounding layer was 1.3 mm thick and had a material hardness of 52 in Shore D hardness, while the intermediate layer was 1.1 mm thick and had a material hardness of 62 in Shore D hardness.
[0043] [Table 1]
[0044] Details of the core materials are as follows. The numbers in the table indicate parts by weight. "Polybutadiene A": Product name "BR01" manufactured by JSR Corporation "Polybutadiene B": Product name "BR51" manufactured by JSR Corporation "Organic peroxide": Dicumyl peroxide, trade name "Percumyl D" manufactured by NOF Corporation "Barium sulfate": Product name "Barico #100" manufactured by Hakusui Tech "Zinc oxide": Product name "Zinc oxide 3 types" manufactured by Sakai Chemical Industry Co., Ltd. "Zinc acrylate": Manufactured by Nippon Shokubai Co., Ltd. "Water": Distilled water, manufactured by Wako Pure Chemical Industries, Ltd. "Pentachlorothiophenol zinc salt": Wako Pure Chemical Industries, Ltd.
[0045] Details of the materials used for the cover (enveloping layer and intermediate layer) are as follows. The numbers in the table indicate parts by weight. "HPF1000": Ionomer made by Dupont "Himilan 1605": Sodium ionomer, manufactured by Dow Mitsui Polychemicals "Himilan 1557": Zn-based ionomer, manufactured by Dow Mitsui Polychemicals "Himilan 1706": Zn-based ionomer, manufactured by Dow Mitsui Polychemicals
[0046] Next, an outermost layer having a thickness of 0.8 mm was coated by injection molding using the resin materials I to IV for the outermost layer shown in Table 2 below. The Shore D hardness of each of the resin materials I to IV is shown in the same table. Although not shown in the figure, numerous dimples were formed on the outer surface of the outermost layer at the same time as the injection molding.
[0047] [Table 2]
[0048] Details of the cover (outermost layer) materials are as follows. The numbers in the table indicate parts by weight. The explanation for "Himilan" is the same as in Table 1. "TPU1" and "TPU2" are trade names of DIC Covestro Polymer, ether-type thermoplastic polyurethanes. "Nucrel": An ethylene copolymer manufactured by Mitsui Dow Polychemicals "AM7329": Ionomer resin manufactured by Dow Mitsui Polychemicals
[0049] Elastic work recovery rate of the cover (outermost layer) To measure the elastic work recovery rate of the outermost layer, a flat plate with the same composition and thickness as the cover material was used as the sample, and a Toyo Corporation ultra-microhardness tester "G200" was used as the measuring device. The measurement conditions were as follows: Indenter: Berkovich indenter (material: diamond, angle α: 130.06°) ·Load F: 100mN Loading time: 15 seconds ·Holding time: 20 seconds ·Unloading time: 15 seconds The elastic work recovery rate is calculated by the following formula based on the indentation work load Welast (Nm) due to the return deformation of the coating film and the mechanical indentation work load Wtotal (Nm). Elastic work recovery rate = Welast / Wtotal × 100(%)
[0050] Formation of paint layer (coating film) Next, the paint having the paint composition shown in Table 3 below was applied to the surface of the outermost layer, on which numerous dimples were formed, using an air spray gun to form a paint layer (coating) 15 μm thick to produce the golf balls of each example.
[0051] Elastic work recovery rate of paint layer The elastic work recovery rate of the paint layer is measured using a 50 μm thick coating sheet. The measurement device used is an ultra-microhardness tester "ENT-2100" manufactured by Elionix, and the measurement conditions are as follows: Indenter: Berkovich indenter (material: diamond, angle α: 65.03°) Load F: 0.2mN Loading time: 10 seconds ·Holding time: 1 second ·Unloading time: 10 seconds The elastic work recovery rate is calculated by the following formula based on the indentation work load Welast (Nm) due to the return deformation of the coating film and the mechanical indentation work load Wtotal (Nm). Elastic work recovery rate = Welast / Wtotal × 100(%)
[0052] [Table 3]
[0053] [Synthesis example of polyester polyol (A)] In a reaction apparatus equipped with a reflux condenser, a dropping funnel, a gas inlet tube, and a thermometer, 140 parts by mass of trimethylolpropane, 95 parts by mass of ethylene glycol, 157 parts by mass of adipic acid, and 58 parts by mass of 1,4-cyclohexanedimethanol were charged, and the mixture was heated to 200-240°C with stirring, and heated (reacted) for 5 hours. After that, a "polyester polyol (A)" with an acid value of 4, a hydroxyl value of 170, and a weight average molecular weight (Mw) of 28,000 was obtained.
[0054] In Examples 1 to 5 and Comparative Examples 1 and 2, the "polyester polyol (B)" was not mixed, and only the "polyester polyol (A)" was dissolved as the main component in butyl acetate, as shown in Table 3. The nonvolatile content of this solution was 27.5% by mass.
[0055] In Comparative Example 3, 27 parts by mass of the polyester polyol solution was mixed with 3 parts by mass of "polyester polyol (B)" ("NIPPOLAN 800" manufactured by Tosoh Corporation, solid content 100%) and an organic solvent (butyl acetate) to form a base material. This mixture had a non-volatile content of 30.0% by mass.
[0056] [Measurement of molecular weight (Mw and Mn)] The molecular weight was measured by the following device. Equipment: Tosoh Corporation High-speed GPC equipment HLC-8220 Column: TSK-GEL G2000H manufactured by Tosoh Corporation XL " and "TSK-GEL G4000H XL " and two connected Column temperature: 40℃ Detector: Differential refractometer Eluent:THF Column flow rate: 0.6 ml / min
[0057] Next, in Examples 1 to 5 and Comparative Examples 1 and 2, as the isocyanate of the curing agent, "Duranate TPA-100" (NCO content 23.1%, non-volatile content 100%) manufactured by Asahi Kasei Corporation, which is an isocyanurate of hexamethylene diisocyanate (HMDI), and "Duranate E402-80B" (NCO content 7.6%, non-volatile content 80%) manufactured by Asahi Kasei Corporation, which is an adduct of HMDI, were used. In Comparative Example 3, only HMDI nurate was used as the isocyanate of the curing agent. The mixing ratio (mass%) of the nurate and the adduct in each Example and Comparative Example is as shown in Table 3. Ethyl acetate and butyl acetate were added as organic solvents, and the amount (concentration) of the isocyanate was adjusted to the value shown in the same table with respect to the total amount of the curing agent including the solvent, to prepare the paint.
[0058] The coating appearance of the golf balls of each of the Examples and Comparative Examples was evaluated according to the following criteria, and the results are shown in Table 4.
[0059] Appearance evaluation of ball surface after sand abrasion test About 4 kg of sand with a size of about 5 mm was placed in a pot mill with an outer diameter of 210 mm, and 15 balls were placed in the pot mill. The mixture was then stirred in the ball mill at a rotation speed of 50 to 60 rpm for 120 minutes. After that, the balls were removed from the pot mill, and the ball appearance was evaluated according to the following criteria. 〔Judgment criteria〕 ◎: No noticeable damage such as peeling or dirt on the ball surface ○: There are small scratches or stains on the ball surface. ×: The ball surface has significant scratches, peeling due to wear, dirt, or loss of luster.
[0060] Appearance evaluation of ball surface after sand and water abrasion test Sand with a size of about 5 mm and about 4 kg of water were placed in a pot mill with an outer diameter of 210 mm, and 15 balls were placed in the pot mill. The mixture was then stirred in the ball mill at a rotation speed of 50 to 60 rpm for 120 minutes. The balls were then removed from the pot mill, and the ball appearance was evaluated according to the following criteria. 〔Judgment criteria〕 ◎: No noticeable damage such as peeling or dirt on the ball surface ○: There are small scratches or stains on the ball surface. ×: The ball surface has significant scratches, significant peeling due to wear, or noticeable dirt or loss of luster.
[0061] [Table 4]
[0062] From the results of the golf ball physical properties in Table 4, the following can be considered. The golf balls of Examples 1 to 5 all gave good results in the sand abrasion test and the sand-water abrasion test, and it is apparent that the coating appearance was good. In contrast, in Comparative Examples 1 and 2, the ball surfaces in the sand abrasion test were good, but the ball surfaces in the sandy-water abrasion test showed noticeable peeling due to abrasion, dirt, loss of luster, etc. In Comparative Example 3, the ball surface in the sandy-water abrasion test was good, but the ball surface in the sand abrasion test showed noticeable peeling due to abrasion, dirt, loss of luster, etc.
Claims
1. A golf ball having a core and a cover consisting of one or more layers covering the core, with the cover having an outermost layer of a paint layer formed from a paint composition, each layer of the cover being formed from a resin composition, the resin composition having an elastic work recovery rate of 35% or more, the paint composition being a paint composition mainly composed of a urethane paint consisting of a polyol as a main agent and a polyisocyanate as a hardener, the polyol consisting of only one type of polyester polyol, the polyisocyanate including two types of hexamethylene diisocyanate, an isocyanurate and an adduct, and the paint composition having an elastic work recovery rate of 70% or more.
2. 2. The golf ball of claim 1, wherein the coating composition has an elastic work recovery rate of 80% or more.
3. 3. The golf ball according to claim 1, wherein the mixing ratio (A) / (B) of the isocyanurate (A) of hexamethylene diisocyanate to the adduct (B) is from 95 / 5 to 40 / 60 by mass.
4. 2. The golf ball of claim 1, wherein the elastic work recovery rate (W1) of said coating composition and the elastic work recovery rate (W2) of each layer of said cover are such that the value of W1-W2 is 50% or less.
Citation Information
Patent Citations
Golf ball
JP1988164966A
Golf ball
JP2000051403A
Golf ball coating material and golf ball using the same
JP2002053799A
Coating composition for golf ball and golf ball using the same
JP2003253201A
Golf ball
JP2011067595A